Ferroelectricity at the Nanoscale Basics and Applications - Fridkin, Vladimir; Ducharme, Stephen (NanoScience and Technology,, 2014)
The investigation of nanosized ferroelectric films and ferroelectric nanocrystals has attracted much attention during the past 15 - 20 years. There is interest in the fundamental and applied aspects. The theoretical basis is connected with the development of the Landau-Ginzburg-Devonshire (LGD) mean field and the first principles theories to the ultrathin ferroelectric films with thickness in the vicinity of critical size. Important potential applications are possible nanosize ferroelectric films in non-volatile memories, microelectronics, sensors, pyroelectric and electro-optic devices. This new area of research of ferroelectricity is still in impetuous development and far from completion. Many topics elucidated  need generalization. The book contains theory and experimental data for a wide range of ferroelectric materials.